2015
DOI: 10.1097/olq.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Human Papillomavirus 16 L1, E6, and E7 Seropositivity and Oral Human Papillomavirus 16 Infection

Abstract: Background Individuals with HPV infections can develop IgG antibodies to HPV proteins including the L1 capsid and E6 and E7 oncoproteins. Evidence on whether L1 antibodies reduce the risk of cervical HPV infection is mixed, but this has not been explored for oral HPV infections. Antibodies to HPV16’s E6 oncoprotein have been detected in some oropharyngeal cancer cases years prior to cancer diagnosis, but it is unknown if these antibodies are associated with oral HPV16 DNA. Methods Enzyme linked immunosorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…While the prevalence of detecting HPV in OSCC was 46.5% in a total of 4680 samples from 94 studies [12], we found that among MD Anderson head and neck cancer cases, HPV16 was detected in approximately 25% of the tumors in the oral cavity, and 80% in oropharynx [15]. For HPV-positive tumors, HPV16 has been identified in 90-95% of the tumors followed by HPV31, 33 and 18 [16 ]. It has been suggested that certain subgroups of OSCC patients are more likely to be HPV16-positive due to effect of potential genetic variants on HPV infection rates.…”
Section: Prevalence Of Hpv In Osccmentioning
confidence: 76%
See 1 more Smart Citation
“…While the prevalence of detecting HPV in OSCC was 46.5% in a total of 4680 samples from 94 studies [12], we found that among MD Anderson head and neck cancer cases, HPV16 was detected in approximately 25% of the tumors in the oral cavity, and 80% in oropharynx [15]. For HPV-positive tumors, HPV16 has been identified in 90-95% of the tumors followed by HPV31, 33 and 18 [16 ]. It has been suggested that certain subgroups of OSCC patients are more likely to be HPV16-positive due to effect of potential genetic variants on HPV infection rates.…”
Section: Prevalence Of Hpv In Osccmentioning
confidence: 76%
“…In addition, other studies also have demonstrated that HPV infection, particularly HPV16, was associated with an increased risk of OSCC, independent of exposure to alcohol and tobacco [20,24]. In a multi-institutional international study of 1670 cases and 1732 controls, Herrero and colleagues found that HPV16 L1, E6, and E7 seropositivity was a significant risk for OSCC [16 ]. In our matched pair analysis at our institution, we found 40.8% of 120 patients with squamous carcinoma of the head and neck to be HPV-16 seropositive but only 9.2% of matched cancer-free controls (adjusted OR = 6.7, 95% CI = 3.0-14.9) [17].…”
Section: Association Of Hpv With Risk Of Osccmentioning
confidence: 93%
“…Of course, high‐risk HPV infection can be a transient phenomenon and detection alone may not be sufficient to provide a causal association. Many studies have previously shown the presence of HPV subtypes even in normal oral cavity tissue . Gillison et al .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HPV 16 in oral rinse samples from healthy adults ranges from 1.0% to 7.6% (21, 22). Only a fraction of those with oral HPV infection will develop HPV-positive OPC after many years.…”
Section: Natural History Of Hpv-related Oropharyngeal Cancermentioning
confidence: 99%